2020
DOI: 10.31349/revmexfis.66.364
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of fractional-order Lü chaotic oscillators for voice encryption

Abstract: In this paper, the encryption improvement via modulation of the fractional order chaotic oscillators state variables, is presented. A network of N-coupled fractional order Lü chaotic oscillators, is synchronized. A voice message is encrypted via additive encryption, by using a state variable of the synchronized network. The selected state variable is modulated and used to encrypt the message again. The results are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…4) The voice cryptosystem presented in this research has a higher security level than the voice cryptosystems suggested in [10], [11], [13], [14], and [17] because of its large key space.…”
Section: Introductionmentioning
confidence: 95%
“…4) The voice cryptosystem presented in this research has a higher security level than the voice cryptosystems suggested in [10], [11], [13], [14], and [17] because of its large key space.…”
Section: Introductionmentioning
confidence: 95%
“…In this section, we design electronic circuits based on the building blocks of Figure 2 and the fractional integrators of Figure 3 to realize commensurate fractional-order Lü chaotic system, i.e., system with equal fractional order for integrators. A commensurate realization is acceptable to test the functionality and benefits of using the active fractionalorder integrators of Figure 3, but incommensurate fractional-order oscillators, as those reported in [45][46][47] or [48] can also be realized with the proposed approach without increasing hardware requirements. In fact, the proposed approach is an attractive alternative for the design of incommensurate fractional-order oscillators because it is necessary to calculate the parameter A using (17) instead of designing ladder networks.…”
Section: Fractional-order Multiscroll Lü Chaotic Systemmentioning
confidence: 99%
“…Chaos synchronization has garnered substantial interest and research over the last few years because of its tenacity in numerous fields, including secure communication, physical science, chemical reactors, and information processing. Numerous intriguing discoveries have been found thus far on chaotic synchronization [9][10][11][12][13]. However, the widely held research is based on synchronization asymptotically.…”
Section: Introductionmentioning
confidence: 99%